Insights into mechanism of aerobic granulation in sequencing batch reactor - Wang, Zhiwu (2010)
Aerobic granulation is a novel environmental biotechnology recently developed for treating a wide spectrum of wastewater. Although extensive research effort has been dedicated to the development of aerobic granules in sequencing batch reactor (SBR), the mechanism responsible for aerobic granulation still remained unclear. Thus, this study attempted to address a basic question of what were the potential driving forces of aerobic granulation in SBR.